Hand washing in operating room: a procedural comparison - Alessia Stilo; Gianmarco Troiano; Lucia Melcarne; Maria Eufemia Gioffrè; Nicola Nante; Gabriella Messina; Pasqualina Laganà (Epidemiology, Biostatistics and Public Health)
BACKGROUND Hand washing has been considered a measure of personal hygiene for centuries and it is known that an improper hand hygiene by healthcare workers is responsible for about 40% of nosocomial infections. Therefore, surgical hand preparation is a critical element for healthcare safety in order to reduce microbial contamination of  surgical wound in case of non detected break of the gloves. The aim of our study is to evaluate the efficacy three antiseptics: Povi-iodine scrub; EPG (Ethanol, Hydrogen Peroxide, Glycerol, recommended by WHO), and common marseille soap type in a liquid formulation.